A CRITICAL ASSESSMENT OF THE PRACTICE OF INTERNAL COMMUNICATION: THE CASE OF AWASH BANK S.C - Mesfin Bogale Gebremeskel (Galaxy International Interdisciplinary Research Journal, 2022)
The study's main goal was to evaluate Awash Bank Share Company's internal communication. The study included a mixed research design, a hybrid communication satisfaction questionnaire, and an in-depth interview. SPSS was used to analyze the quantitative data using descriptive statistics. According to the study's results, downward communication and uneven information flow characterize internal organizational communication at Awash Bank Head Office Addis Abeba. The communication channels are likewise solely intended for downward communication. Awash Bank's internal organizational communication must be improved. Internal organizational communication primarily aims to inform staff on bank rules, procedures, manuals, and updates. Communication is poor both above and downward. The flow of information and communication channels is inefficient. It is revealed that the overall internal organizational communication practice at should be revisited and channels need to be tailored.